Analisis Spasio-Temporal COVID-19 Di Kabupaten Semarang Pada Bulan September Hingga November Tahun 2021 - Kartika Dian Pertiwi; Tri Widyaningsih; Pramudya Teguh Sucipto (Universitas Ngudi Waluyo, 2022)
ABSTRACTThe percentage of active Covid-19 cases in Semarang Regency is 20.97%, exceeding the national percentage of 14.8%. Implementation of Covid-19 surveillance using control management based on spatial or regional data to determine distribution patterns and facilitate monitoring of the spread of the Covid-19 virus. This type of research is descriptive using a cross sectional approach. The sampling technique used was purposive sampling with a total sample of 241 cases. The data collection tool uses the GPS Essential app. Spatio-temporal analysis using ArcGis 10.7. The results of the study using the Nearest Neighbor Test Analysis showed the pattern of distribution of positive confirmed cases of Covid-19 in September the value of Nearest Neighbor Ratio = 0.465340 which means <1 indicates that the distribution pattern is clustered. Pattern of Distribution of Positive Confirmation Cases of Covid-19 In October the value of Nearest Neighbor Ratio = 1.001926 which means > 1 indicates that the distribution of positive confirmed cases of Covid-19 in Semarang Regency is random. Distribution Pattern of Positive Confirmation Cases of Covid-19 In November the value of Nearest Neighbor Ratio = 1.103031 which means >1 indicates that the distribution pattern is random. The prevalence of Covid-19 cases in Semarang Regency from September to November 2021 has decreased. The pattern of distribution of positive confirmed cases of Covid-19 in September is clustered, October is random, and November is random. Suggestions for the Semarang District Health Office to improve close contact tracing and cross-sectoral collaboration in collecting data on Covid-19 cases.Â Keywords: Spatio-Temporal, Covid-19, Semarang District Health Office.